New Mutation in 23S rRNA Gene Associated with High Level of Azithromycin Resistance in Neisseria gonorrhoeae - Galarza, Patricia G. (2010)
Fil: Galarza, Patricia G. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas. Centro Nacional de Referencia en Enfermedades de Transmisión Sexual; Argentina.